Written Languages in Moldavia during the Reign of Peter Rareş (1527–1538, 1541–1546) - Knoll, Vladislav (Studia Ceranea, 2022)
The language of the Moldavian books and chancery documents written during the reign of Peter Rareş (1527–1538, 1541–1546) shows an unneglectable variability depending on the purpose, addressee and format of the texts. Using all kinds of preserved texts from this period, we have tried to describe this variability focusing on the texts written in the Cyrillic script. These texts are evaluated according to three criteria: spelling, morphosyntax and vocabulary. The most prestigious variety was the Trinovitan (Tărnovo) variety of Middle Church Slavonic. Its shape in the texts, belonging to the common Church Slavonic legacy, shows the lowest impact of the Moldavian linguistic environment. The original Church Slavonic bookish texts composed in Moldavia (Macarie’s Chronicle, Enkomion to St John the New, colophons and inscriptions) show a variable proportion of Moldavian spelling and morphosyntactic markers. The chancery documents can be characterised by blending of Church Slavonic and Ruthenian (Ukrainian-based) elements. Except the Ruthenian-based documents addressed to Poland, the chancery documents are basically Church Slavonic shaped with Ruthenian infiltrations on the level of some fixed formulas, function words and few lexical items. Moreover, Slavonic letters sent to Transylvania show tiny Wallachian Slavonic influence, manifested by forms of Serbian chancery origin. Monastery charters combine CS-shaped Ruthenian formulas with Trinovitan Church Slavonic formulas, partly shared with colophons and inscriptions. Thus, the Moldavian written legacy shares common elements both with the Wallachian milieu (e.g. Romanian Cyrillic spelling of proper names, Romanian impact on morphosyntax, specific terminology etc.) as well as with a broader Ruthenian area (mainly the eastern part of the Polish-Lithuanian Union).